Aplikasi Pengoreksian Kesalahan Bahasa Indonesia Menggunakan Metode Jaro Winkler Distance Dan Levenshtein Distance Berbasis Web - Nurva Agustin, Sandra; Mufarrihah, Iftitaahul; Rahman Prehanto, Dedy (Inovate, 2022)
Writing errors in typing documents very often occur in writing articles, scientific journals, lectures or final assignments. Typing errors cannot be avoided. There are several factors, including the location of the letters close to each other on the keyboard, errors in the corrections made by the word processor, accidental errors such as slip of a finger. For this reason, an application for error categorization in Indonesian was made to make it easier to check documents. The purpose of this study is to design a correction system using the Jaro Winkler Distance and Levenshtein Distance methods. The Jaro winkler distance algorithm is basically a method that compares the similarity of the constituent characters of two strings and the Levenshtein Distance algorithm is a string metric to measure the difference between two sequences. The results of this research are in the form of typing error correction web where the user can correct .doc / .docx formatted documents. Key words : jaro winkler distance, levenshtein distance.